Impact of Relationship Marketing on Brand Loyalty with Reference to Nepalese Commercial Banks - Upadhyay, Mahesh Prasad (Journal of Balkumari College, 2022)
In this study, the researcher makes the efforts to examine impact of relationship marketing strategies followed by Nepalese Commercial Banks make the customers brand loyal toward them. Primary data and secondary data are used for the study. After analyzing the data, Nabil bank ranked the 1st position. The most of the Chitwan customers are loyal towards the Nabil Banks due to good relation and trust of customers.